Papua New Guinea : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Papua New Guinea. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
The COVID-19 pandemic erupted just as the government was beginning to implement wide-ranging fiscal, foreign exchange, structural, and governance measures under a Staff-Monitored Program (SMP). The authorities have reaffirmed their commitment to these reforms, but the impact of the crisis is generating balance of payments and fiscal gaps of 4 and 3 percent of GDP, respectively. In the near term, risks are primarily on the downside, especially if there is a widespread local outbreak of the virus. Papua New Guinea's longer-term outlook remains positive, largely reflecting the likelihood of major resource sector projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet